In my father's country : an Afghan woman defies her fate - Wahab, Saima (Crown Publishers, 2012)
Relates the author's decision, years after her father was taken away by the KGB, to relocate to her uncle's home in America, where she pursued an education and worked as an interpreter before becoming a cultural adviser for the U.S. Army.